Forecasting the short end of the term structure of interest rates - Graham, Austin (Kansas State University, 2010)
This thesis examines the properties of two short-term interest rates: the federal funds rate and the rate of return on 90-day Treasury securities (T-Bills). Findings indicate strong evidence of cointegration among the two series. This result leads us to consider whether future movements in T-bill returns are predictable using the same methods used to predict the target federal funds rate. The “Taylor Rule,” introduced by Taylor (1993), assumes the Federal Reserve considers inflation and the output gap in their deliberation of how to adjust the federal funds target rate. We do an in-sample analysis followed by an out-of-sample forecasting comparison. Findings show that, in addition to inflation and the output gap, the unemployment rate and stock market contain valuable information for forecasting future T-bill rates.
Keywords: forecast; VAR; Federal Reserve; interest rates; T-bill; economics; Economics, Finance (0508); Economics, History (0509); Economics, Theory (0511)